Forced Vibration Analysis of Laminated Composite Plates under the Action of a Moving Vehicle - Hossein Abbaszadeh Mobaraki; Ramazan-Ali Jafari-Talookolaei; Paolo S. Valvo; Reza Haghani Dogaheh (Fracture and Structural Integrity)
This paper provides a finite element analysis of laminated composite plates under the action of a moving vehicle. The vehicle is modeled as a rigid body with four suspension systems, each consisting of a spring-dashpot. Overall, the vehicle possesses three degrees of freedom: vertical, rolling, and pitching motions. The equations of motion of the plate are deduced based on first-order shear deformation theory. Using the Euler-Lagrange equations, the system of coupled equations of motion is extracted and solved by using the Newmark time discretization scheme. The algorithm is validated through the comparison of both the free and forced vibration results provided by the present model and exact or numerical results reported in the literature. The effects are investigated of several system parameters on the dynamic response.